2019
DOI: 10.1021/acscatal.9b03322
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Mediated Photocatalytic Aerobic Dehydrogenation of N-heterocycles by Surface-Grafted TiO2 and 4-amino-TEMPO

Abstract: Herein, the visible-light-induced dehydrogenation of N-heterocycles such as tetrahydroquinolines, tetrahydroisoquinolines, and indolines in O2-containing suspensions of a commercially available titanium dioxide photocatalyst yielding the corresponding heteroarenes is presented. 4-Amino-2,2,6,6-tetramethylpipiridinyloxyl (4-amino-TEMPO) was found to exhibit a beneficial role, as it increased the yield and improved the selectivity of the dehydrogenation reaction. Both the selectivity and the yield are further en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 63 publications
0
83
0
Order By: Relevance
“…Moreover, the spin trapping technique was not only used to detect and monitor the formed reactive species such as the oxygen and nitrogen reactive radicals [94,99] during the photocatalytic degradation process, but also is employed within the mechanistic pathway to monitor and/or to be involved in controlling the experimental conditions during the photocatalysis organic synthesis [82,[100][101][102]. The involvement of TEMPO derivative radical within a mechanistic pathway of the synthesis reaction is assumed to act as a selective redox mediator involved in reactions of the generated reactive oxygen species.…”
Section: Spin Trapping In the Liquid Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the spin trapping technique was not only used to detect and monitor the formed reactive species such as the oxygen and nitrogen reactive radicals [94,99] during the photocatalytic degradation process, but also is employed within the mechanistic pathway to monitor and/or to be involved in controlling the experimental conditions during the photocatalysis organic synthesis [82,[100][101][102]. The involvement of TEMPO derivative radical within a mechanistic pathway of the synthesis reaction is assumed to act as a selective redox mediator involved in reactions of the generated reactive oxygen species.…”
Section: Spin Trapping In the Liquid Phasementioning
confidence: 99%
“…The involvement of TEMPO derivative radical within a mechanistic pathway of the synthesis reaction is assumed to act as a selective redox mediator involved in reactions of the generated reactive oxygen species. Balayeva et al [101] studied the visible-light-induced dehydrogenation of N-heterocycles such as tetra-hydroquinolines, tetrahydroisoquinolines, and indolines compounds on the surface of TiO 2 in an aerated system yielding the corresponding heteroarenes compounds. In this study, the authors found that 4-amino-TEMPO exhibits a beneficial role, as it improved the yield and increased the selectivity of the dehydrogenation reaction.…”
Section: Spin Trapping In the Liquid Phasementioning
confidence: 99%
“…Such an adsorbed organic substrate can react irreversibly with the photogenerated holes, minimizing the undesired electron/hole recombination [150]. Even though H2 can be formed simultaneously with other processes, e.g., the organic synthesis of organic compounds [160,161], however, such processes should not be considered as a dual function process [130]. The reforming process can be considered as a dual function photocatalysis process only when some requirements have been met: (i) H2 is mainly derived from the reduction of water and (ii) the targeted organic molecules are pollutants, or their oxidation aimed to synthesize value-added products, such as aldehyde, organic acid, and imine [130,162].…”
Section: Photocatalytic Water Splitting Vs Photocatalytic Reformingmentioning
confidence: 99%
“…Perylene diimide (PDI) has been widely used as a basic structural unit for fabricating organic photo‐functional materials in recent years due to its unique optical and electronic properties . Compared to some semiconductor photocatalysts (TiO 2 and C 3 N 4 ), easy chemically modified PDIs can be used as functional photocatalysts in various photo‐promoted chemical transformation.…”
Section: Figurementioning
confidence: 99%